The Application of Science Concepts in Management Research Reports Based on Scientific Truth - Hady, Hamdy; Henderi, Henderi; Putri, Dian Mustika (APTISI Transactions on Management (ATM), 2018)
The management activity of research report writing requires sufficient knowledge in its preparation. A researcher must learn about the management of understanding scientific concepts, as well as management of research reports that are based on scientific truth. In this study, 1 (one) method was used, namely a literature study of 10 (ten) to support the understanding of scientific concepts according to experts. The concept is a general idea that represents perceived understanding on the basis of reason and logic by someone who then forms a meaning deductively or inductively. Whereas knowledge is what is known or the results of work know. Then scientific truth is related to the quality of knowledge, where every knowledge possessed is viewed from the type of knowledge that is built. Thus scientific truth is an important point in scientific reporting, as the basic foundation of accurate management of report writing and must be displayed in every corner of the report. It is hoped that this research can assist researchers in compiling research reports. Keywords: Management, Science, Scientific Truth, Research Reports.